1998
DOI: 10.1038/sj.onc.1201728
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p21 and p27 in the regulation of CDK activity and cell cycle progression in the regenerating liver

Abstract: In tissue culture systems, p21 and p27 inhibit cyclindependent kinase (CDK) activity and cell cycle progression in response to numerous stimuli, but little is known about their involvement in cell growth in vivo. We examined the modulation of CDK activity by these proteins after 70% partial hepatectomy (PH), an in vivo model of synchronous hepatocyte cell cycle progression. After PH in BALB/c mice, p21 was induced during the prereplicative (G1) phase and was maximally expressed after peak hepatocyte DNA synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
183
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(222 citation statements)
references
References 45 publications
(85 reference statements)
35
183
0
4
Order By: Relevance
“…Although further studies are therefore required to further elucidate this relationship, the concept of cellular senescence warrants further consideration as replicative arrest affecting a large proportion of hepatocytes might significantly compromise the regenerative capacity of the liver in these cases. Furthermore, previous studies have suggested that p21 plays a key role in regulation of hepatocyte G1 phase progression and that transgenic mice with forced hepatic expression of p21 have markedly impaired regeneration after partial hepatectomy 29, 30…”
Section: Discussionmentioning
confidence: 99%
“…Although further studies are therefore required to further elucidate this relationship, the concept of cellular senescence warrants further consideration as replicative arrest affecting a large proportion of hepatocytes might significantly compromise the regenerative capacity of the liver in these cases. Furthermore, previous studies have suggested that p21 plays a key role in regulation of hepatocyte G1 phase progression and that transgenic mice with forced hepatic expression of p21 have markedly impaired regeneration after partial hepatectomy 29, 30…”
Section: Discussionmentioning
confidence: 99%
“…36 DNA synthesis, cyclins/CDK activation and S phase gene expression occur earlier in transgenic p21 waf1 knockout mice than in wild type mice following partial hepatectomy. 37 In contrast, transgenic mice with hepatic overexpression of p21 waf1 demonstrate diminished liver size and markedly impaired hepatocyte proliferation following resection. 38 Little is known about the mechanisms regulating p21 waf1 expression in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Another type of cell cycle suppressor, the WAF1/Kip1 family members, suppress Cyclin/Cdk complex activity. p21 WAF1 (Harper et al, 1993;Li et al, 1994) interacts with the Cyclin D/Cdk4 complex and the p27 Kip1 homolog (Polyak et al, 1994) suppresses the Cyclin E/Cdk2 complex (Sherr and Roberts, 1995;Reynisdottir and Massague, 1997;Albrecht et al, 1998). Thus, the cell cycle progression from G1 phase to S phase is initiated by phosphorylated Rb, which is regulated by Cyclin/Cdk complexes and multiple suppressor proteins.…”
Section: Introductionmentioning
confidence: 99%